Tracing the origins of verlan in an early nineteenth century text? - Bach, X (Cambridge University Press (CUP), 2017)
This article examines early attestations of verlan and related backward slangs in French in the nineteenth century. Its main contribution is the edition and analysis of the only known text, a letter, written with features of verlan before the twentieth century. This largely predates other attested forms of verlan. The principles underlying this early form of verlan are shown to be different from contemporary verlan, as is much other early evidence, though all forms have the syllable as their basic unit. The letter is evidence that backward slangs can originate in the education system as much as in the underworld of thieves.